ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH DALAM MENINGKATKAN LOYALITAS NASABAH KREDIT (Studi Kasus pada Debitur Kredit Produktif di Bank Jateng KCP Jatipuro) - Retno Susanti, Kusuma Febbry Andari, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2018)
The purpose of this study is to analyze (1) the significance of affectingthe quality of service to customer satisfaction. (2) the significance of theinterest rate of credit on customer satisfaction. (3) the significance of theeffect of customer satisfaction on customer loyalty. (4) significance affectsthe quality of service to customer loyalty. (5) the significance of the effect oflending rate on customer loyalty. (6) customer satisfaction in mediationaffects the quality of service to loyalty. (7). customer satisfaction in mediatinginfluence. The research was conducted at Jateng KCP Jatipuro Bank.Population of 300 people. Sample of 60 people, with snowball samplingtechnique and convenience sampling technique. Data completion techniquewith questionnaire Technical analysis using path analysis model andmediation with Sobel Test. The results of research proved by quality.Significant to customer satisfaction, significant interest rates on customerloyalty, significant interest rates on customer loyalty, customer satisfactionvariables moderation influence service quality variables with customerloyalty, and customer satisfaction variables.Keywords: service quality, credit interest rate, satisfaction, loyaltyÂ